Deep retrofit approaches: Managing risks to minimise the energy performance gap - Topouzi, M; Owen, A; Killip, G; Fawcett, T (European Council for an Energy-Efficient Economy, 2019)
Energy use in buildings remains a significant part of overall energy demand. Deep renovation projects, delivered at scale, remain a challenging task to achieve a lower carbon building stock.The complexity of building renovation beyond standards and building specifications is related to inherent characteristics of buildings which require distinct project management techniques. While there are now more projects focusing on achieving operational performance, there is still very little research on the management of the renovation and retrofit process itself. Recognising that each project working on an existing building is unique in type, timing, energy goals and the roles/characteristics of people involved, the aim of this paper is to add to the current debate of how intervention approaches (one-off or over-time, whole-house, fabric-first room-by-room, measure-by-measure) are promoted by different policies, and with what impact. The paper discusses the complexity of a deep renovation project in terms of planning and management and the ways current policies can lead to unintended consequences in the short and long term, as well in lock-in effects that contribute to energy performance, and to the gap between designed and actual energy performance. Using a typology of risks, the issues associated with renovation processes and technologies were explored in a sample of cases studies from deep retrofits across the EU. The evidence from these shows that despite holistic planning for renovation, interventions tend to be carried out in phases. These contrasting time dimensions and the different retrofit approaches are discussed with risk profiles for each retrofit project, suggesting how risks emerge throughout a project. A series of risk mitigation strategies are suggested which, taken in combination to suit a specific project’s risk profile, may serve to reduce and potentially eliminate the building renovation energy performance gap.